(3GdaJGhi GdCfbQhjIs - (3GdCfbQhj GdCfchQj, eMeO Hf MSjf, J (B1098 (3g`s ((3HjG RGjGOs)
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH GdWgGQI hjJhVC HeGA GdSeGA hGdeQGO HeGA GdSeGA eGA GdeWQ hGdfLG hGdKdL hGdHQO EPG cGf eJbGWQG hYf CHj jhSa jLhR hEf de jcf eJbGWQGs
(3BNQgG (B:s
(3ajchf GdeQGO Cfg GdfUQI aj GdYGbHI bGd GdSQNSj hdC ddhGQK fhY hdGjI hHGdSHH GdNGU hgh GdbQGHI ceG ddG jKHJ GdhdGjI ddcGaQ Ydi GdeSde dG jKHJ ddeSde Ydi dcGaQ ef VhA GdSQGLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 246s
(3eYLe GdeDdajf (B3 / 246s
(3NdGUI GdCKQ (B4 / 314s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs